ASSESSING DIFFERENT STRATEGIES FOR CONTROLLING WEEDS IN MAIZE CULTIVATION WITHIN THE DERIVED SAVANNA AGRO-ECOLOGY IN NIGERIA - Olagbemi Peter AFON; Oluwakemi Olajumoke AJAYI; Adesike Oladoyin OLAYINKA; Emmanuel Ajibola OLAGUNJU; Gabriel Olulakin ADESINA (Journal of Plant Development)
Maize is the second most cultivated crop in Nigeria in terms of hectares of land. In the world it ranks fourth amongst cultivated cereals. However, its cultivation is faced with different challenges ranging from biotic to abiotic factors. Weeds are one of the biotic factors that threaten maize yield.in the field because of the cost and labor associated with it control. Hence, using Randomized Complete block Design, a two-year study was carried out to assess different strategies that are used in controlling weeds in the derived savanna agroecological zone of Nigeria at Ogbomoso Girls High School, Ogbomoso (8°9'N, 4°15'E) and Surulere North LCDA Igbon (8°14'N, 4°18'E). The total land area used was 13 m x 23 m with plot size 2 m x 3 m in three replicates. Eight treatments were used which are weedy plots, weed free, manual I, manual II, Pre-emergence herbicide (Glyphosate-1.08 kg a.i ha-1), Post-emergence herbicide (Nicrosulfuron- 0.12 kg a.i ha-1), Cowpea+Maize and Potato+Maize) to give 24 plots. Data collected were on weed parameters and maize yield. Weed parameters include: weed population, dry weed biomass and weed control ratio at 3, 6 and 9 weeks after sowing. Parameters on maize yield include number of seeds per cob, grain weight of seeds per cob, cob length, weight of 100 seeds per plot, grain weight per plot and grain weight per hectare. The result on weed parameters shows that there is no significant difference in the weed control rating and the dry weed biomass of manual weeding, pre-emergence herbicide, post emergence herbicide, cowpea+ maize, and potato + maize. Though there was significant difference in the weed population among the treatments. For maize yield (GWH), there was no significant difference between Manual II and the use of post emergence herbicide. Also the yield obtained from pre-emergence herbicide, potato+maize, cowpea+maize were not significantly different. Hence, it is recommended that legumes and potatoes can be used rotationally to control weeds in maize plots.